2015
DOI: 10.7554/elife.06328
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid remodeling by LPCAT3 enriches arachidonate in phospholipid membranes and regulates triglyceride transport

Abstract: Polyunsaturated fatty acids (PUFAs) in phospholipids affect the physical properties of membranes, but it is unclear which biological processes are influenced by their regulation. For example, the functions of membrane arachidonate that are independent of a precursor role for eicosanoid synthesis remain largely unknown. Here, we show that the lack of lysophosphatidylcholine acyltransferase 3 (LPCAT3) leads to drastic reductions in membrane arachidonate levels, and that LPCAT3-deficient mice are neonatally letha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
179
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 190 publications
(212 citation statements)
references
References 64 publications
6
179
1
1
Order By: Relevance
“…4, A and B) could explain the compensation for defective cholesterol uptake in Lpcat3-deficient enterocytes. It has been shown that global deletion of Lpcat3 at an early stage of development results in the accumulation of lipid droplets in enterocytes (9,10). However, we did not find any difference in lipid levels in the small intestine of Lpcat3-deficient and control mice (Fig.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…4, A and B) could explain the compensation for defective cholesterol uptake in Lpcat3-deficient enterocytes. It has been shown that global deletion of Lpcat3 at an early stage of development results in the accumulation of lipid droplets in enterocytes (9,10). However, we did not find any difference in lipid levels in the small intestine of Lpcat3-deficient and control mice (Fig.…”
Section: Discussioncontrasting
confidence: 50%
“…It has been reported that ablation of Lpcat3 reduces arachidonoyl-PCs in the embryonic and postnatal small intestine (9,10). We found that Lpcat3 deficiency in the small intestine significantly decreased polyunsaturated PCs, including 16:0/18:2, 18:1/18:2, 18:1/18:3, and 18:0/20:4 (Table 1), and this modification could disrupt the structural integrity and fluidity of the plasma membrane.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Another example, which is extreme, is the formation of lipoprotein particles, which are particular forms of LDs made in the ER lumen. The budding of triglyceride-containing lipoproteins requires the local production of polyunsaturated phospholipids by LPCAT3 (Hashidate-Yoshida et al, 2015). We have found that these phospholipids specially allowed the budding of triglyceride droplets ( Figure 2E).…”
Section: Discussionmentioning
confidence: 81%